Entwicklung einer Online-Intervention für die Versorgung von sich selbstverletzenden Jugendlichen und jungen Erwachsenen = Development of an online intervention for adolescents and young adults engaging in nonsuicidal self-injury - Edinger, Alexandra; Koenig, Julian; Bauer, Stephanie; Moessner, Markus; Fischer-Waldschmidt, Gloria; Herpertz, Sabine; Resch, Franz; In-Albon, Tina; Koelch, Michael; Plener, Paul L.; Schmahl, Christian; Kaess, Michael (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2020)
Development of an Online Intervention for Adolescents and Young Adults Engaging in Nonsuicidal Self-injury Nonsuicidal self-injury (NSSI) is a prevalent phenomenon in adolescence. Despite the existence of effective psychotherapeutic interventions, the majority of affected adolescents and young adults do not receive any treatment. Structural (e. g., no specific interventions, limited resources, limited accessibility) as well as individual factors (e. g., low help-seeking behavior) impede access to adequate clinical care for adolescent NSSI. Online interventions offer the possibility to provide specific interventions independent of one's location or local healthcare structures. Because of its high confidentiality and accessibility, the Internet also reaches adolescents with low help-seeking behavior. There is already evidence for online interventions concerning different mental health issues, like depression and anxiety. However, regarding NSSI, there are no effective, online interventions. Thus, we developed an online intervention based on an already evaluated short term program specific for adolescents and young adults with NSSI within the German STAR consortium (STAR: Self-Injury - Treatment, Assessment, Recovery). Within a randomised controlled trial, the intervention will be evaluated regarding its efficacy.
Gesehen am 27.10.2020